Demand for secondary school characteristics: Evidence from school choice data in Hungary - Thomas Wouters; Zoltán Hermann; Carla Haelermans (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2018)
We estimate preferences for school tracks in upper secondary education in Hungary. We consider travel time, school SES composition, school level (in terms of peer quality) and school quality (in terms of added value). We find that students have stronger preferences for school SES composition and school level, rather than school quality (which may be harder to observe). Furthermore, these preferences vary between high and low ranked schools, indicating students use heuristics in the process of compiling their ranked preference list.
Keywords: I21; I24; 330; school choice; school composition; school quality; rank-ordered logit